Membaca Realitas Infodemi Covid-19 di Indonesia - Aurelius RL Teluma (Universitas Mataram, 2020)
The Covid-19 Infodemic is a massive flood of information, both accurate and inaccurate, making it difficult for people to find reliable sources and guidance when they need it to overcome Covid-19's disease. This paper seeks to read the reality of infodemic in Indonesia by processing and to restate and to interpret data from the Covid19 Infodemics Observatory project on the dynamics of Indonesian citizens' tweets concerning Covid-19 for the period January 21, 2020 - July 22, 2020. The data can be obtained freely on the https://covid19obs.fbk.eu/#/. The analysis shows that globally, from January 21 to July 22, 2020, there were more than 365 million tweets related to Covid-19. In Indonesia, the highest number of infodemic tweets produced was 114,000 tweets per day on March 15, 2020. Even so, only 608 tweets were confirmed as reliable facts, and 87 tweets were verified as unreliable facts. There are still too few tweets that are categorized as reliable facts, and there are still many that are classified as unreliable facts. It has led to the high Infodemic Risk Index in Indonesia, reaching the level of 0.77 from the scale of 0.00 - 1.00 on January 25, 2020. The large gap between the number of tweets and news reliability occurred during the Covid-19 pandemic from January to July 2020.